Circulating Vitamin D Levels and the Risk of Atrial Fibrillation: A Two-Sample Mendelian Randomization Study - Yang, Shengyi; Zhi, Hong; Sun, Ying; Wang, Lina (Frontiers in Nutrition, 2022)
Aims: We performed two-sample Mendelian randomization (MR) analysis to evaluate the association between serum vitamin D levels and AF risks. Methods: Data on the single nucleotide polymorphisms (SNPs) related to vitamin D, 25-hydroxyvitamin D and AF outcome were obtained from UK Biobank study, SUNLIGHT consortium and the latest meta-analysis of GWASs with six independent cohorts, respectively. MR analysis were performed to obtain the estimates, followed by using inverse variance weighted (IVW) method, weighted median method, Maximum likelihood, MR-egger method and MR-PRESSO methods. Results: The IVW estimate showed that genetically predicted Vitamin D and 25-hydroxyvitamin D levels were not causally associated with the risk of AF with two models. The association was consistent in complementary analyses. Conclusions: Our MR finding suggested no genetic evidence of serum vitamin D levels was significantly associated with AF risk. Further researches are necessary to explore the potential role and mechanisms of circulating serum vitamin D levels on AF.